2022
DOI: 10.3390/foods11040561
|View full text |Cite
|
Sign up to set email alerts
|

A Biosurfactant from Candida bombicola: Its Synthesis, Characterization, and its Application as a Food Emulsions

Abstract: The present study aimed to produce a biosurfactant from Candida yeast cultivated in a low-cost medium made of sugar-cane molasses (5%), frying oil waste (5%), and corn steep liquor (5%). Initially, the production at the flask-scale was investigated and then scaled up in bioreactors to 1.2, 3.0, and 50 L to simulate a real production scale. The products obtained an excellent reduction in surface tensions from 70 to 29 mN·m−1 in the flask-scale, comparable to 33 mN·m−1 in the 1.2-L reactor, to 31 mN·m−1 in the 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…On the other hand, the reduction of interfacial tension is considered as another parameter that indicates the production of biosurfactant (dos . In this sense, excellent interfacial tension of 2.3 mN/m was verified with nhexadecane, since values below 7 mN/m are referred as good in the literature (Luna, et al, 2013;Pinto, et al, 2022).…”
Section: Surfactant Propertiesmentioning
confidence: 77%
“…On the other hand, the reduction of interfacial tension is considered as another parameter that indicates the production of biosurfactant (dos . In this sense, excellent interfacial tension of 2.3 mN/m was verified with nhexadecane, since values below 7 mN/m are referred as good in the literature (Luna, et al, 2013;Pinto, et al, 2022).…”
Section: Surfactant Propertiesmentioning
confidence: 77%
“…However, emulsions formed by crude BE/BS from L. brevis S4 and L. plantarum S5 were stable after 72 h of incubation at room temperature, as no significant variations ( p > .05) in emulsification indexes were noticed. This emulsion stabilizing ability of BE/BS could be explained by the fact that the adsorption of BE/BS at the interface between oil and air prevents the coalescence of droplets through electrostatic repulsion (Pinto et al, 2022 ; Rudy, 2011 ). Hence, the Ostwald ripening leading to the coalescence of droplets and an irreversible increase in the droplets' size (Karami et al, 2022 ) is reduced.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the reduction of interfacial tension is considered as another parameter that indicates the production of biosurfactant (dos Santos, et al, 2021). In this sense, interfacial tension of 16.6 mN/m was verified and it was considered as an acceptable value, since in the literature high values of interfacial tension are referred to as those above 18 mN/m (Luna, et al, 2013;Pinto, et al, 2022). Previously, Luna et al (2013) and Ribeiro et al (2020) reported interfacial tension values of 12.5 and 13.99 mN/m for biosurfactants produced by C. sphaerica UCP 0995 and Saccharomyces cerevisiae URM 6670, respectively.…”
Section: Production Of Biosurfactant In 2 L Of Waste-based Mediummentioning
confidence: 93%
“…Biosurfactants can be produced by several microbial groups, including bacteria, filamentous fungi, and yeasts. In the case of the latter, most works report the use of representatives of the Candida genus (Luna, et al, 2015;Lima, et al, 2017;Rubio-Ribeaux, et al, 2020;Pinto, et al, 2022). The yeast Issatchenkia orientalis, previously known as Pichia kudriavzevii, Candida krusei or C. glycerinogenes (Douglass, et al, 2018;Zwirzitz, et al, 2021), has shown promising potential for the production of Research, Society and Development, v. 11, n. 10, e364111032851, 2022 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v11i10.32851 3 surfactant molecules (Katemai, et al, 2008;Csutak, et al, 2012).…”
Section: Introductionmentioning
confidence: 99%